Literature Study: School and Community Partnership Model to Improve the Quality of Educational Environment - Afrianti, Heni; Viona, Elsa; Efriyadi, Efriyadi (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2024)
The purpose of this study is to describe the school and community partnership model to improve the quality of the educational environment. This study is a literature study of data collection methods in the form of journals and scientific articles related to research studies. The analysis used in this study includes a review of the latest research findings and screening of relevant research materials. This study reveals that school and community partnership models, such as the Caring School Project (Rudolph, 2009) and the School Community Council Model (Diehl et al., 2005), the Ohio Community Collaborative Model (OCCMSI) (Anderson-Butcher et al., 2008) and the National Partnership School Network (NNPS) Model (Sanders et al., 2005) show that school-community partnerships are not only limited to academic teaching but also include the social and economic well-being of students. Effective collaboration between schools and communities can create broader support for students, increase family involvement, and resolve local challenges that affect the quality of education. Educational success depends not only on the school's internal efforts but also on how they work together with the community. Good collaboration between schools, families, and community organizations can create a more supportive educational environment conducive to student success.